TRANSFORMATIONS OF A SYSTEM STATE UNDER THE SEQUENCE OF CONDITIONS - Andrianov, Yuri; Kapustin, Alexandr; Kudryavtsev, Igor; Fishchenko, Petr (Journal of Applied Engineering Science, 2019)
The algorithm of transformation of a system states is established on the basis of applying the methods of mathematical modelling and theoretical mechanics, providing preservation of a stationary property of the system. The form and the sizes of dangerous zones for a moving exosystem (a person in a medical exoskeleton) are determined as well. This will allow to produce the maximum allowable velocity, avoiding both lateral overturning of the exosystem, and collision with obstacles during its movement.